US farm policy and trade: The inconsistency continues - Glauber, Joseph W.; Sumner, Daniel A. (American Enterprise Institute, 2017)
Trade has always been important for US agriculture, but over the past 50 years, US producers and consumers have become increasingly linked to global markets. This paper provides an overview of US international trade policies and discusses the trade implications and economic consequences of these policies. This paper also outlines policy reforms, many due to trade agreements and the World Trade Organization’s (WTO) influence, which have lowered tariffs, increased trade, and fostered income growth for farms and lower prices for consumers. Despite such progress, distortions remain, notably in high tariffs for a handful of commodities, price and income subsidies, government-sponsored crop insurance, and dairy subsidy programs. These policies continue to transfer billions of dollars from taxpayers and consumers to farms and agribusinesses, distort crop prices in global markets, and expose the United States to challenges under WTO rules. As Congress prepares for the 2018 Farm Bill, the impact of farm policies on international markets should be a central concern to help build prosperity for producers and consumers.